The Effect of Capital Structure on Profitability in Health Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 Period - Darul Hikam Idrissyah; Retno Kurnianingsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study intends to examine the influence of capital structure on Profitability in health sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The capital structure used in this study was proxied with DAR and DER, while Profitability was measured by ROA. This study uses a quantitative approach with multiple linear regression analysis methods. The study sample consisted of 18 companies through purposive sampling techniques from a total population of 35 companies. The results of the analysis showed that the DAR variable had a negative and significant influence on Return on assets (ROA), while the DER did not show a significant influence. Simultaneously, these two independent variables have been shown to have a significant effect on ROA. These findings confirm the importance of managing capital structures, especially the use of debt in influencing the company's Profitability performance in the health sector.